Whole-plant trait networks reveal elevational optimization of resource strategies: integration drives distribution in woody saplings - Wang, Zuhua; Li, Haibo; Yang, Chuandong; Wang, Jugang; Chen, Fen; Liu, Min (Frontiers in Plant Science, 2025)
IntroductionPlant trait networks (PTNs) reveal integrated adaptation strategies, but how elevational stress gradients reshape PTN architecture and influence species distribution remains unclear.MethodsWe analyzed 14 leaf, stem, and root traits across 37 woody sapling species along a 600 – 2200 m elevational gradient on Mt. Fanjingshan, China. We linked PTN metrics (connectivity, modularity, hub traits) to environmental drivers and species distributions.ResultsPTN integration increased with elevation, evidenced by declining average path length (R² = 0.93, P = 0.008) and graph diameter (R² = 0.92, P = 0.011), indicating intensified trait coordination at higher elevations. Modularity peaked at mid-elevations (unimodal pattern: R² = 0.97, P = 0.017), reflecting heightened trade-offs between stress tolerance and resource acquisition. Crucially, litter depth and soil phosphorus—not climate—were the primary drivers of PTN structure, jointly explaining 84.2% of variation (P = 0.011) and promoting integration via root-hub traits (specific root length, specific root area). Species distribution was strongly correlated with PTN efficiency (84.8% explained variance, P = 0.038), driven by reduced graph diameter, greater litter depth, and lower temperature.DiscussionThese findings indicate that elevational stress selects for highly integrated PTNs optimized by belowground trait hubs and microhabitat buffering, highlighting litter-soil interactions as critical mediators of species distributions under climatic constraints.